Traditional eye medicine use in microbial keratitis in Uganda: a mixed methods study [version 2; peer review: 2 approved] - Arunga, Simon; Asiimwe, Allen; Olet, Eunice Apio; Rugunda, Grace Kagoro; Ayebazibwe, Bosco; Onyango, John; Newton, Robert; Leck, Astrid; Macleod, David; Hu, Victor H; Seeley, Janet; Burton, Matthew J (Wellcome Open Research, 2019)
Background: Traditional eye medicine (TEM) is frequently used to treat microbial keratitis (MK) in many parts of Africa. Few reports have suggested that this is associated with a worse outcome. We undertook this large prospective study to determine how TEM use impacts presentation and outcome of MK and to explore reasons why people use TEM for treatment in Uganda. Methods: In a mixed method prospective cohort study, we enrolled patients presenting with MK at the two main eye units in Southern Uganda between December 2016 and March 2018 and collected information on history, TEM use, microbiology and 3-month outcomes. We conducted qualitative interviews with patients, carers traditional healers on reasons why people use TEM. Outcome measures included presenting vision and at 3-months, comparing TEM Users versus Non-Users. A thematic coding framework was deployed to explore reasons for use of TEM. Results: Out of 313 participants enrolled, 188 reported TEM use. TEM Users had a delayed presentation; median presenting time 18 days versus 14 days, p= 0.005; had larger ulcers 5.6 mm versus 4.3 mm p=0.0005; a worse presenting visual acuity median logarithm of the minimum angle of resolution (Log MAR) 1.5 versus 0.6, p=0.005; and, a worse visual acuity at 3 months median Log MAR 0.6 versus 0.2, p=0.010. In a multivariable logistic regression model, distance from the eye hospital and delayed presentation were associated with TEM use. Reasons for TEM use
Keywords: Microbial Keratitis; Traditional Eye Medicine; Traditional Healers; Blindness; Uganda